Antimicrobial effects of Zingiber officinale extracts against multi-drug resistant Acinetobacter baumannii clinical isolates recovered from hospitalized patients in ICU - HassasYeganeh, Shirin; Hosseini Doost, Seyed Reza; Goudarzi, Mehdi (Archives of Advances in Biosciences, 2018)
Zingiber officinale as an herbal medicinal plant is used for its potential antimicrobial activity against different microbial pathogens. Multi-drug resistant Acinetobacter baumannii as an important nosocomial pathogen especially in intensive care units is responsible for a wide range of serious infections in humans. The purpose of this study was to investigate the antimicrobial activity of Z. officinale extracts on growth of A. baumannii strains isolated from hospitalized patients in intensive care units in Tehran, Iran. During a 9 month study, 50 multi-drug resistant A. baumannii isolates were recovered from patients in ICU. The Kirby-Bauer disk diffusion method was used to determine resistance patterns of Multi-drug resistant A. baumannii isolates to antimicrobial agents. Micro-broth dilution method was used to determine the antimicrobial activity of methanol, acetone, and chloroform extracts of Z. officinale against multi-drug resistant A. baumannii isolates. The results of susceptibility testing showed that all the isolates were resistant to ceftriaxone, ciprofloxacin, ceftazidime, cefotaxime, cefepime and piperacillin. Resistance to colistin was found to be low (4%) and exhibited good antibacterial activity against tested isolates. This study’s findings revealed that methanol, acetone, and chloroform extracts of Z. officinale have anti-bacterial activity against tested bacterial isolates. Based on the results, the chloroform extracted fraction showed the highest level of activity at a minimal inhibitory concentration of 25 mg/ml on multi-drug resistant A. baumannii (64%). The minimal inhibitory concentration of ginger extract was as low as 3.2 mg/ml. The present study indicated that Z. officinale extracts, at various concentrations could be used as an antibacterial agent for treatment of patients in ICUs.